Fast-chargeable lithium-ion batteries by μ-Si anode-tailored full-cell design - Taeyong Lee; Min Ji Seong; Hyo Chul Ahn; Minsung Baek; Kiho Park; Jihoon Oh; Taehoon Choi; Jang Wook Choi (Proceedings of the National Academy of Sciences, 2025)
Silicon (Si) anodes have long been recognized to significantly improve the energy density and fast-charging capability of lithium-ion batteries (LIBs). However, the implementation of these anodes in commercial LIB cells has progressed incrementally due to the immense volume change of Si across its full state-of-charge (SOC) range. Here, we report an anode-tailored full-cell design (ATFD), which incorporates micrometer-sized silicon (μ-Si) alone, for operation over a limited, prespecified SOC range identified as 30−70%. This range allows homogeneous (de)lithiation throughout the electrode, accompanied by an acceptable level of volume change. The ATFD-based cell exhibits 21.3% higher gravimetric energy density than that of its graphite-based counterpart in a commercial 18650 cylindrical cell and 84.6% capacity retention after 500 cycles even at a fast-charging rate of 3 C. This study indicates that the partial, intermediate SOC operation of the μ-Si anode can markedly increase the energy density and boost the fast-charging capability of a LIB cell, a challenging task in traditional cell engineering.